2013
DOI: 10.1021/ed400177r
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Impact of Silver Nanoparticles on Brassica rapa: An Environmental Nanoscience Laboratory Sequence for a Nonmajors Course

Abstract: Nanoscience is one of the fast growing fields in science and engineering. Curricular materials ranging from laboratory experiments to entire courses have been developed for undergraduate science majors. However, little material has been developed for the nonmajor students. Here we present a semester-long laboratory sequence developed for a nonmajors course, where students investigate the potential environmental impacts of nanoscience. Students synthesize and characterize silver nanoparticles using green synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…14 Indeed, several studies have shown that Ag NPs can produce toxic effects on marine life. For example, the presence of Ag NPs in the water system leads to the poisoning of microorganisms, 15 zebra fish, 15 aquatic plants, 16 and human cells (skin keratinocytes and lung fibroblast cells). 17,18 Herein, we explore the transformation of citrate-stabilized Ag NPs in the presence of water containing phosphate anions.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Indeed, several studies have shown that Ag NPs can produce toxic effects on marine life. For example, the presence of Ag NPs in the water system leads to the poisoning of microorganisms, 15 zebra fish, 15 aquatic plants, 16 and human cells (skin keratinocytes and lung fibroblast cells). 17,18 Herein, we explore the transformation of citrate-stabilized Ag NPs in the presence of water containing phosphate anions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Indeed, several studies have shown that Ag NPs can produce toxic effects on marine life. For example, the presence of Ag NPs in the water system leads to the poisoning of microorganisms, zebra fish, aquatic plants, and human cells (skin keratinocytes and lung fibroblast cells). , …”
Section: Introductionmentioning
confidence: 99%
“…With the increasing incorporation of nanotechnology into the science and engineering curriculum, innovative approaches have been used to add laboratory components to coursework. Although other topics such as nanoparticle dose quantification, interfacial properties, , and interactions with the environment, , are starting to gain momentum, many of the current approaches are still focused on nanoparticle synthesis. The proposed set of experiments, as part of a newly developed “Nano and Biointerfaces” course, focused on another equally important aspect of nanotechnology by familiarizing students with nanoparticle characterization techniques and the required analysis after each experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their widespread uses, vivid size-dependent colors, and ease of synthesis, Ag NPs are featured in many nanotechnology lab experiments described in this Journal and elsewhere. Most procedures are appropriate for a general chemistry lab course, and some can be performed by high school students. Students can observe the antimicrobial properties of Ag NPs , and their detrimental effects on plants and brine shrimp . A recent article in this Journal shows a simple method for illustrating the toxicological effects of other nanoparticles on beans …”
Section: Introductionmentioning
confidence: 99%
“…12−18 Most procedures are appropriate for a general chemistry lab course, and some can be performed by high school students. Students can observe the antimicrobial properties of Ag NPs 19,20 and their detrimental effects on plants 21 and brine shrimp. 22 A recent article in this Journal shows a simple method for illustrating the toxicological effects of other nanoparticles on beans.…”
Section: ■ Introductionmentioning
confidence: 99%